2020
DOI: 10.1152/ajpcell.00195.2020
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on surfactant protein A: cellular function in lung and kidney disease development

Abstract: Pulmonary surfactant is a heterogeneous active surface complex made up of lipids and proteins. The major glycoprotein in surfactant is surfactant protein A (SP-A), which is released into the alveolar lumen from cytoplasmic lamellar bodies in type II alveolar epithelial cells. SP-A is involved in phospholipid absorption. SP-A together with other surfactant proteins and phospholipids prevent alveolar collapse during respiration by decreasing the surface tension of the air/liquid interface. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 50 publications
0
22
0
1
Order By: Relevance
“…Another study demonstrated that the addition of ILC2s can make AMs express more M2 macrophages-related markers in vitro ( 88 ). Postnatal adaptation to breathing depends on pulmonary surfactant being synthesized and secreted by type 2 alveolar epithelial cells (AEC2) ( 89 ). Promoted by M2 macrophages, AEC2 continuously proliferate and differentiate to accelerate alveolar formation ( 90 ).…”
Section: Crosstalk Between Ilc2s and M2 Macrophages During Lung Develmentioning
confidence: 99%
“…Another study demonstrated that the addition of ILC2s can make AMs express more M2 macrophages-related markers in vitro ( 88 ). Postnatal adaptation to breathing depends on pulmonary surfactant being synthesized and secreted by type 2 alveolar epithelial cells (AEC2) ( 89 ). Promoted by M2 macrophages, AEC2 continuously proliferate and differentiate to accelerate alveolar formation ( 90 ).…”
Section: Crosstalk Between Ilc2s and M2 Macrophages During Lung Develmentioning
confidence: 99%
“…Pulmonary function parameters and radiographic features on computed tomography images are currently important determinants for the diagnosis and severity and prognosis assessment for IPF. However, accumulating evidence shows that blood levels of certain lung-specific macro-molecules, such as Krebs von den Lungen-6 (KL-6, also known as mucin-1, a glycoprotein expressed on the cell membrane of type 2 alveolar cells) and surfactant protein A (SPA, also secreted by type 2 alveolar cells), are also correlated with the severity of fibrosis and may serve as biomarkers for determining the clinical aspects of IPF [ 36 40 ]. While pulmonary function parameters are commonly used to assess the efficacy of antifibrotic treatment, the utility of these, as well as clinical and bio-chemical, characteristics for predicting therapeutic response and adverse outcomes during antifibrotic treatment remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactant protein (SP) -A has been recently recognized as an immunomodulator in urinary tract infections ( 84 ). SP-A facilitates pathogen clearance by enhancing opsonic and non-opsonic phagocytosis via binding to SP-A receptor in macrophages ( 84 ).…”
Section: Resultsmentioning
confidence: 99%